NGO Capacity Building Initiatives: Impacts and Constraints in Enhancing Teachers’ Competence for Managing Learning Environments in Tanzanian Public Secondary Schools - Ngonyani, Humphrey; Galabawa, Justinian J. C.; Nasibu Kamando, Amina (Papers in Education and Development, 2024)
This study employed a qualitative research approach with a case study design to investigate capacity-building programmes (CBPs) provided by nongovernmental organisations (NGOs) in Tanzanian public secondary schools. Specifically, the study focused on the NGOs’ initiatives, impacts, and constraints towards enhancing teachers’ competence in managing the learning environment. In-depth interviews and focused group discussions were used to collect data from 50 teachers. The findings revealed that the CBPs improved teachers’ competence in designing and organising physical learning spaces, cultivating positive classroom relationships, and leveraging information and communication technology to enrich the learning environment. However, the programmes were constrained by a short duration of delivery and a lack of continued support. The study recommends the adoption of appropriate interventions by NGOs and the government to ensure the sustainability of NGO-supported capacity-building programmes, thereby fostering lasting impacts on teachers’ capacity to manage the learning environment in public secondary schools. Keywords: Capacity building, non-state actors, professional development, classroom management